2022
DOI: 10.1111/1751-7915.14102
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of yeast Erg1 expression and terbinafine susceptibility by iron bioavailability

Abstract: Ergosterol is a specific sterol component of yeast and fungal membranes.Its biosynthesis is one of the most effective targets for antifungal treatments.However, the emergent resistance to multiple sterol-based antifungal drugs emphasizes the need for new therapeutic approaches. The allylamine terbinafine, which selectively inhibits squalene epoxidase Erg1 within the ergosterol biosynthetic pathway, is mainly used to treat dermatomycoses, whereas its effectiveness in other fungal infections is limited. Given th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This study primarily focused Unexpectedly, the knockout of the ROX1 gene and overexpression of the UPC2-1 gene led to a decrease in patchoulol production. Jordá et al [33] observed increased mRNA and protein levels of the ERG1 (squalene epoxygenase-encoding gene) gene after knocking down the ROX1 gene. We guessed that an enhancement in the metabolic pathway of epoxidized squalene may have competed with the patchoulol pathway for the precursor FPP, resulting in reduced patchoulol production.…”
Section: Improving the Production Of Patchoulol By Modifying Transcri...mentioning
confidence: 99%
“…This study primarily focused Unexpectedly, the knockout of the ROX1 gene and overexpression of the UPC2-1 gene led to a decrease in patchoulol production. Jordá et al [33] observed increased mRNA and protein levels of the ERG1 (squalene epoxygenase-encoding gene) gene after knocking down the ROX1 gene. We guessed that an enhancement in the metabolic pathway of epoxidized squalene may have competed with the patchoulol pathway for the precursor FPP, resulting in reduced patchoulol production.…”
Section: Improving the Production Of Patchoulol By Modifying Transcri...mentioning
confidence: 99%
“…This has been demonstrated in S. cerevisiae , where iron deficiency increases the cell's susceptibility to terbinafine, a compound that inhibits squalene epoxidase Erg1 and so disrupts the ergosterol biosynthetic pathway. This has been attributed to both a decrease in Erg1 translation and the lanosterol‐induced degradation of Erg1 under iron deprivation conditions (Jordá et al, 2022 ).…”
Section: Simultaneous Inhibition Of Fungi By Multiple Antifungals In ...mentioning
confidence: 99%